2019
DOI: 10.3390/vetsci6040086
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalences of Newly Discovered Porcine Pestiviruses in German Pig Farms

Abstract: Several novel porcine pestiviruses that are linked to disease outbreaks in commercial pig farms were discovered

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
(48 reference statements)
0
16
0
3
Order By: Relevance
“…Other important methods that are used to assist in the diagnosis of infectious diseases are serological tests. The tests described for APPV infection are IFI [59], virus neutralization [55], and indirect enzyme-linked immunosorbent assay (ELISA) to the NS3, E2, and E rns proteins [50,55,58,61]. These tests have many important applications, and they can be used for population-based epidemiological studies and monitoring of infection in the herd; the tests also feature easy execution and low cost.…”
Section: Diagnostic Methods Of Appvmentioning
confidence: 99%
See 2 more Smart Citations
“…Other important methods that are used to assist in the diagnosis of infectious diseases are serological tests. The tests described for APPV infection are IFI [59], virus neutralization [55], and indirect enzyme-linked immunosorbent assay (ELISA) to the NS3, E2, and E rns proteins [50,55,58,61]. These tests have many important applications, and they can be used for population-based epidemiological studies and monitoring of infection in the herd; the tests also feature easy execution and low cost.…”
Section: Diagnostic Methods Of Appvmentioning
confidence: 99%
“…Additionally, in this same study, the highest (17.5%; 35/200) prevalence of positive samples was in Italy. Michelitsch et al [59], by indirect immunofluorescence test (IFI), found an antibody prevalence of 16.3% (182/1115) in pig serum samples in Germany. In Switzerland, 1080 sera from pigs for slaughter, which were obtained between 1986 and 2018, were evaluated by qRT-PCR, and the APPV genome was detected in 13% [77].…”
Section: Epidemiology and Implications In Pig Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus was isolated for the first time in 2003 from a large Australian integrated pig farm during an outbreak of sudden death in young pigs, followed by an increase in stillbirth [2,3]. Although BuPV represents a potential threat to commercial pig farming, it has not yet been reported from any other region or country [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Besides horizontal transmission through oronasal pathway, APPV could also be vertically transmitted by transplacental infection [4,5]. One retrospective study showed that 41.8% (51/122) sampled pig farms and 16.3% (182/1115) porcine serum samples could be detected antibodies against APPV in Germany [28]. The infection rate of piglets born from infected sows could reach 16%-100%, the mortality rate of piglets from infected herds could reach 30%, and the survival rate of weanling piglets could drop 10% per sow, showing that APPV could cause huge economic losses to pig industry [7,29].…”
mentioning
confidence: 99%